(untitled) (Islas, 2021)
This scientific article is framed within the line of sociolinguistics, a discipline that allows us to identify the way a community speaks, as well as its incidence in the transformation processes that occur within the language, reflected in the linguistic variety. The social variables taken are: gender, level of education and age; as for the linguistic variants, a fixed variant was worked on: a general fixed variant: phraseology and specific variants such as adjective locutions. The main objective is to find out if this type of lexical resources is used significantly in the Barranquilla-speaking community. For this purpose, a corpus based on the Diccionario Fraseológico Documentado del Español Actual (2009) by Manuel Seco, Olimpia Andrés and Gabino Ramos was used. The sample consisted of 48 men and 48 women, three levels of education and four age groups. The methodology employed is of a sociolinguistic nature, where the investigative approach is based on the information analysis. In particular, the result derived from the social variables, in line with the linguistic variant prepositional syntagm plus adjective, allowed us to demonstrate that women make a greater use of adjective locutions. The identities they entail tend to imply a boundary marking function through a particular use of language and a highly marked internal coherence, thanks to the mastery of certain linguistic features.